Modified 'Stent-Graft Sandwich' Technique for Treatment of Isolated Common Iliac Artery Aneurysm in Patient With Marfan Syndrome - Yoshida, Ricardo de Alvarenga [UNESP]; Yoshida, Winston Bonetti [UNESP]; Kolvenbach, Ralf; Bahdur Vieira, Paulo Roberto [UNESP] (Elsevier B.V., 2012)
Isolated iliac artery aneurysms are rare in the general population (0.03%) and represent 2% of all abdominal aneurysms, and the association with Marfan syndrome is even rarer. We report a Marfan syndrome case with an isolated common iliac artery aneurysm treated by using a modified 'stent-graft sandwich' technique, with preservation of the internal iliac artery perfusion. The modified 'stent-graft sandwich' technique involves building an appropriate proximal neck just in the common iliac artery for fittingly housing two new stent-grafts inside, both deployed simultaneously and each one going to both distal iliac arteries (internal and external).